Protective effect of valproic acid on cultured motor neurons under glutamate excitotoxic conditions. Ultrastructural study - Nagańska, Ewa; Matyja, Ewa; Taraszewska, Anna; Rafałowska, Janina (Folia Neuropathologica, 2015)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder that involves the upper and lower motor neurons and leads to the patient’s death within 5 years after diagnosis. Approximately 2 per 100,000 people worldwide are affected every year. The only FDA-approved drug available for medical treatment is riluzole. It slows the disease progression and improves limb function and muscle strength for 3-4 months. Thus, looking for new therapeutic agents is a pressing challenge. Valproic acid (VPA) is a short-chain fatty acid, widely used for the treatment of seizures and bipolar mood disorder. The beneficial effect of VPA has been documented in different neurodegenerative experimental models, including amyotrophic lateral sclerosis (ALS). The real mechanisms underlying numerous beneficial effects of VPA are complex, but recently it has been postulated that the neuroprotective properties might be related to direct inhibition of histone deacetylase (HDAC). The aim of this ultrastructural study was to evaluate the beneficial effect of VPA on the spinal cord motor neurons (MNs) in a glutamate (GLU)-induced excitotoxic ALS model in vitro. It had been previously documented that chronic GLU excitotoxicity resulted in various MN injuries, including necrotic, apoptotic and autophagic modes of cell death. The present results demonstrated the neuroprotective properties of VPA associated with inhibition of apoptotic and autophagic changes of spinal MNs in a model of neurodegeneration in vitro.